Peningkatan Kapasitas Komunitas Remaja Partan Melalui Pelatihan Manajemen Konflik dan Negosiasi di Bogor - Erialdy Erialdy; Diana Syatri (Civiliza Publishing, 2025)
This training aims to improve adolescents' understanding of conflict dynamics, develop assertive communication skills, and introduce common interest-based negotiation strategies. This training activity is designed with a participatory approach, involving a community of 200 adolescents. The implementation of the program includes providing theoretical materials on conflicts, conflict resolution simulations, and negotiation practice exercises. The results of the evaluation showed a significant improvement in participants' understanding of conflict management concepts, assertive communication skills, and skills in reaching agreement through negotiation. In addition, participants successfully developed an action plan to manage conflicts at the family, organization, and community levels. This article not only discusses the results of the training but also identifies the challenges faced during the implementation of the program as well as provides recommendations for the sustainability of these activities. With this program, it is hoped that teenagers will be able to create an environment conducive to collaboration.